2018
DOI: 10.1021/acs.jafc.8b03951
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Enhanced Antioxidant Activity by Hydrogen Sulfide Antagonization of Ethylene in Tomato Fruit Ripening

Abstract: Ethylene (CH) and hydrogen sulfide (HS) play important physiological roles in regulating fruit ripening and senescence. The mechanism of HS in ethylene-induced tomato fruit ripening and senescence is still unknown. Here, we show that exogenous HS reduced the production of superoxide anion (·O), malondialdehyde (MDA), and HO in tomato fruit. Further, additional HS was found to induce the activities of guaiacol peroxidase, catalase, ascorbate peroxidase, and superoxide dismutase compared with CH treatment alone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 42 publications
(78 reference statements)
0
43
0
Order By: Relevance
“…ROS include free radicals, such as O 2− and OH, and non-radicals, such as H 2 O 2 and 1 O 2 , which induce oxidative damage in cells [86]. The increase in the H 2 O 2 content is a typical plant response to arsenic exposure [87], so much so that when arsenic exposure increases, H 2 O 2 levels also increase, being strongly time dependent [15].…”
Section: Discussionmentioning
confidence: 99%
“…ROS include free radicals, such as O 2− and OH, and non-radicals, such as H 2 O 2 and 1 O 2 , which induce oxidative damage in cells [86]. The increase in the H 2 O 2 content is a typical plant response to arsenic exposure [87], so much so that when arsenic exposure increases, H 2 O 2 levels also increase, being strongly time dependent [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing evidence has demonstrated that H 2 S possesses multiple physiological functions during the development of both animals and plants 19,20 . In tomato, limited studies have shown that H 2 S is involved in the auxin-or methane-induced lateral root formation 21,22 , the modulation of fruit ripening via increasing antioxidant activity 23 , and the alleviation of stress caused by salt or excess nitrate through altering the redox status of the stressed plants 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between H 2 S and other signaling molecules, such as NO and ethylene, have also been a focus of recent investigations on the senescence of flowers or ripening of fruits. Hydrogen sulfide alleviates postharvest ripening and senescence of fruits by antagonizing the effect of ethylene [218,219]. In addition, a cooperative effect of H 2 S and NO has been observed on delaying the softening and decay of fruits [220], and the crosstalk between these two gasotransmitters is associated with the inhibition of ethylene biosynthesis [221].…”
Section: H 2 S In Human and Plant Therapiesmentioning
confidence: 99%